Development and Proof of Concept of an Audit Toolkit for the Safe Handling of Cytotoxic Drugs in Low- and Middle-Income Countries. (2021) - von Grünigen, Sandrine; Falaschi, Ludivine; Guichard, Nicolas; Fleury-Souverain, Sandrine; Geissbühler, Antoine; Bonnabry, Pascal
Abstract : PURPOSE: Chemotherapies are considered high-risk drugs for patient and staff safety. Considering the rising burden of cancer and the increasing use of chemotherapy drugs in low- and middle-income countries (LMICs), promoting continuous improvements in the safety and quality of practices in these settings is essential. This paper describes the development and proof of concept of a toolkit to audit chemotherapy handling practices in the health care facilities of LMICs. METHODS: A steering committee defined the audit method and the toolkit content. Several checklists were developed to facilitate the audit and data collection. Items included in checklists were derived from key reference works on safe handling. Different tools were validated using Delphi surveys and expert reviews. Audits of pilot sites were performed to test the toolkit's applicability and relevance. RESULTS: The toolkit contains a 134-item global assessment tool for the different processes at each step of the medication pathway and three step-specific observation checklists to assess different health workers' practices during the prescription, preparation, and administration of chemotherapies. The toolkit also proposes using a surface-wipe sampling method to measure any cytotoxic contamination of the immediate environment. The toolkit was tested in three teaching hospitals in Africa. CONCLUSION: The toolkit developed was successfully implemented in a variety of LMIC settings, providing a comprehensive evaluation of the quality and safety of the chemotherapy drug handling practices in participating health care facilities. This toolkit can help facilities in LMICs to implement a new approach to continuously improving the quality and safety of their practices and ultimately ensure patient and staff safety.